2017
DOI: 10.1161/circimaging.116.005242
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Monitoring of Acute Myocarditis Applying Quantitative Cardiovascular Magnetic Resonance

Abstract: Background— Cardiovascular magnetic resonance based on the Lake Louise Criteria is used to make the diagnosis of acute myocarditis. Novel quantitative parametric mapping techniques promise to overcome some of its limitations. We aimed to evaluate quantitative cardiovascular magnetic resonance to detect and monitor acute myocarditis. Methods and Results— Eighteen patients with clinical diagnosis of acute myocarditis (25 years [23–38 years]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 32 publications
8
90
0
1
Order By: Relevance
“…The left ventricular ejection fraction and the end diastolic volume of the left ventricle were not significantly different in the acute patients compared with controls, as we have studied infarct‐type myocarditis. This suggests that the stroke volume (SV) was not on the lower range.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The left ventricular ejection fraction and the end diastolic volume of the left ventricle were not significantly different in the acute patients compared with controls, as we have studied infarct‐type myocarditis. This suggests that the stroke volume (SV) was not on the lower range.…”
Section: Resultsmentioning
confidence: 95%
“…For the comparison of simulation to patient data, we applied the model in a recently published patient cohort . In this study of n = 18 patients with myocarditis, as defined in Ref 28, underwent 2 CMR examinations at 1.5 T. First, in the acute state of the disease (called “acute”) and after 6 months, a follow‐up examination was undertaken in the chronic state (called “healed”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding this question, Luetkens et al [52] reported that there was a significant and consistent decrease in all inflammatory CMR parameters over the course of the disease (p<0.01 for all parameters). Myocardial T1 and T2 relaxation times-indicative of myocardial edema-were the only single parameters showing significant differences between myocarditis patients and control subjects at the 5.5±1.3-week follow-up (native T1: 986.5±44.4 vs. 965.1± www.e-cvia.org 201 [53] reported that although both T2 and T1 mapping reliably detected acute myocarditis, only T2 mapping discriminated between acute and healed stages, underlining the incremental value of T2 mapping.…”
Section: Acute and Chronic Myocarditismentioning
confidence: 99%
“…T2 weighted imaging, T1 -and T2 mapping techniques LLC are now often complemented by novel CMR techniques such as native T1 and T2 mapping as well as extracellular volume fraction (ECV) measurement to provide a higher sensitivity and specificity (46,47). Native T1 mapping values are affected by both edema and extracellular expansion and is therefore able to detect myocarditis at various stages, whereas T2 mapping evaluates free water content that is normally present in the acute phase of myocarditis and then gradually normalizes over months -this is relevant for cardiac caregivers evaluating the course of myocarditis as it is the only technique that can adequately discriminate between myocarditis and noninflammatory cardiomyopathies in patients with symptoms lasting longer than 2 weeks (48,49). A recent meta-analysis by Pan et al (48) comparing the diagnostic performance of ECV, native T1 mapping and T2 mapping versus LLC for detection of acute myocarditis including 17 studies and 1308 subjects, has shown that only native T1 mapping had A c c e p t e d m a n u s c r i p t significantly better sensitivity than LLC, while other parameters had comparable diagnostic performance to LLC and provided distinct advantages for evaluating myocarditis.…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 99%